Analysis of insurance preauthorization requests for BRCA1 and BRCA2 genetic testing: experience of the Humana Genetic Guidance Program. (September 2011) - Shah, Amisha; Harris, Heather; Brown, Trisha; Graf, Michael D; Sparks, Leah; Mullins, Tammy; Bruins, Cari; Prewitt-Eddy, Kira
Published evidence-based guidelines help healthcare providers identify appropriate individuals for BRCA1/2 genetic testing. Health plans often use these guidelines to help make coverage and reimbursement decisions. Humana, a major health plan, launched the Humana Genetic Guidance Program to further facilitate the appropriate use of genetic testing through education.Aim: Identify opportunities to improve medical appropriateness for BRCA1/2 test requests by providing genetic education to providers.Materials & methods: BRCA1/2 insurance preauthorization requests submitted to the program were evaluated against guideline-based coverage criteria.Results: In total, 22% of the requests did not meet criteria, and in approximately a quarter of those requests, the clinical history suggested testing for a different cancer syndrome or another affected relative.Conclusion: This report demonstrates the program's effectiveness and illustrates the need for additional provider education regarding genetic testing from a payer's perspective.